2007
DOI: 10.1016/j.nurt.2006.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Eslicarbazepine Acetate (BIA 2-093)

Abstract: Summary: Eslicarbazepine acetate (ESL) [(S)-(Ϫ)-10-acetoxy-10,11-dihydro-5H-dibenz[b,f]azepine-5-carboxamide], formerly known as BIA 2-093, is a novel central nervous system (CNS)-active compound with anticonvulsant activity. It behaves as a voltage-gated sodium channel (VGSC) blocker and is currently under clinical development for the treatment of epilepsy and bipolar disorder. ESL shares with carbamazepine and oxcarbazepine the dibenzazepine nucleus bearing the 5-carboxamide substitute, but is structurally d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
136
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(137 citation statements)
references
References 18 publications
0
136
0
1
Order By: Relevance
“…In fact, at least in humans this AED is readily converted to S-Lic and R-Lic (Almeida and Soares-da-Silva, 2007). Regarding the fact that OXC is a minor metabolite of ESL in humans, OXC accounts for less than 5% of metabolized ESL, and it is unlikely that high concentrations of OXC as those used in this study will reach the brain.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In fact, at least in humans this AED is readily converted to S-Lic and R-Lic (Almeida and Soares-da-Silva, 2007). Regarding the fact that OXC is a minor metabolite of ESL in humans, OXC accounts for less than 5% of metabolized ESL, and it is unlikely that high concentrations of OXC as those used in this study will reach the brain.…”
Section: Discussionmentioning
confidence: 86%
“…ESL is structurally different at the 10,11-position, and consequently, it is not metabolized to CBZ-10,11-epoxide and, therefore, it is not susceptible to enzyme induction or autoinduction (Bialer, 2006). Moreover, ESL is a once-daily AED (Almeida and Soares-da-Silva, 2007) that is rapidly absorbed and undergoes extensive first-pass metabolism, in humans (Almeida et al, 2005) and mice (Alves et al, 2007), to its main active metabolite, eslicarbazepine (S-Lic), which is responsible for approximately 95% of total systemic drug exposure, and to a lesser extent to Rlicarbazepine (R-Lic) and OXC, (Almeida et al, 2005). Our group previously demonstrated that ESL is less toxic to cultured neurons than CBZ and OXC, namely at high concentrations (0.3 mM).…”
Section: Introductionmentioning
confidence: 99%
“…Eslicarbazepine acetate (ESL) [S-(−)-10-acetoxy-10,11-dihydro-5H-dibenz/b,f/azepine-5-carboxamide], previously known as BIA 2-093, is a novel chiral drug presently completing phase III clinical trials, as add-on therapy in refractory partial epilepsy, and undergoing phase II clinical trials, as monotherapy in partial epilepsy and in bipolar disorder (Almeida and Soares-da-Silva, 2007). ESL is chemically related to CBZ and OXC (Benes et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…9) is an AED second-generation to carbamazepine. It showed efficacy in several animal seizure models both electrically (MES) and chemically (pentetrazole, bicuculline, picrotoxin, 4-aminopyridine) evoked [51]. [52].…”
Section: Eslicarbazepine Acetate (Esl)mentioning
confidence: 99%